IMPLEMENTASI LAPORAN KEUANGAN DAN PERPAJAKAN BERBASIS MICROSOFT EXCEL DALAM PENETAPAN TARGET LABA POLJAM MART - Devi Indah sri (Journal of Applied Accounting And Business, 2026)
The problem of recording financial and tax statements at Poljam Mart that has not been effectively integrated has resulted in difficulties in producing financial and tax reports in accordance with applicable standards and setting the right profit target. In this study, a Microsoft Excel-based financial reporting system was designed and implemented which was prepared in accordance with the EMKM SAK and MSME taxation provisions. The research uses a descriptive qualitative method with a case study approach through the stages of problem identification, data collection, system design, implementation, and evaluation at Poljam Mart. The results of this study show that the developed system is able to improve the accuracy of transaction recording, facilitate the process of preparing financial and tax statements, facilitate the calculation of tax liabilities, and produce more accurate profit information to support the retrieval decision. Overall, the results of the study prove that the application of Microsoft Excel-based financial and tax reports can increase the effectiveness of financial and tax management according to applicable standards and support the determination of profit targets at Poljam Mart.